Person-centered care enhances quality of life among older adults in long-term care settings - Kartinah, Lilis; Permadi, Rangga (Global Indonesia Health Care (GOICARE), 2025)
Background: As aging populations grow, ensuring quality of life in long-term care has become a global priority. Person-centered care (PCC) offers a tailored approach that respects individual values and preferences. Objective: This study investigated the impact of PCC on the quality of life among older adults residing in long-term care facilities in Indonesia. Methods: A mixed-methods design was employed with 82 elderly residents across four facilities. Quantitative data were collected using the WHOQOL-OLD scale pre- and post-intervention, while qualitative insights were gained through in-depth interviews. Results: PCC significantly improved overall quality of life scores, particularly in autonomy and social participation domains (p < 0.05). Residents reported feeling more respected and emotionally secure after the implementation of PCC routines. Conclusion: Person-centered care positively influences the well-being of older adults in institutional care. Training for staff and structural adaptation are essential for sustainable PCC implementation.